Pseudoangiomatous stromal hyperplasia of the breast: a case report of a 12-year-old girl - Eman Almohawes, MD (Radiology Case Reports, 2015)
Pseudoangiomatous stromal hyperplasia (PASH) of the breast is a benign lesion, characterized by a dense proliferation of stromal mesenchymal cells of myofibroblastic origin forming empty, slit-like channels. We report PASH in a 12-year-old girl with a huge rapidly enlarged right breast. Biopsy of the mass showed histopathologic features characteristic of PASH. Immunohistochemical studies revealed diffuse positive membranous immunoreactivity to CD34. Although it is a benign lesion, lumpectomy was performed to minimize the damage from developing breast tissue.